SAEED TEEBI’S WOODLAND: CULTURAL DISPLACEMENT AND DIASPORA - Sari Fitria; Laksmy Ady Kusumoriny; Hekza Astomo; Ahmad Fadilla; Aditya Reza Arifin (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
This study is purposed to reveal cultural displacement and diaspora in Saeed Teebi’s short story, Woodland. This story tells about an Algerian diaspora, Noor, and her experiences for being uprooted from her native country. Noor's experiences exemplify the complicated of mental and physical upheaval which also illustrate the long-lasting effects of relocation on personal identity. Her observations provide insights into the difficulties experienced by people of the diaspora as she makes her way through life in a new cultural setting. This study applies a concept of diaspora by Stuart Hall focusing on cultural displacement experienced by diaspora. This displacement relates to identity construction due to the process of leaving the homeland. Furthermore, a content analysis method is applied in this study. The result of the study shows that Teebi's exploration of Noor's journey sheds light on the diverse dimensions of displacement, providing a nuanced understanding of the diaspora experience. Through Noor's narrative, the study contributes to the broader discussion on the complex nature of identity, belonging, and the persistent echoes of one's homeland in the lives of diaspora individuals.